2019
DOI: 10.1088/1367-2630/ab0756
|View full text |Cite
|
Sign up to set email alerts
|

Extreme velocity gradients in turbulent flows

Abstract: Fully turbulent flows are characterized by intermittent formation of very localized and intense velocity gradients. These gradients can be orders of magnitude larger than their typical value and lead to many unique properties of turbulence. Using direct numerical simulations of the Navier-Stokes equations with unprecedented small-scale resolution, we characterize such extreme events over a significant range of turbulence intensities, parameterized by the Taylor-scale Reynolds number ( l R ). Remarkably, we fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
191
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(214 citation statements)
references
References 47 publications
21
191
2
Order By: Relevance
“…6,7,25,26 Other previous studies visualize isosurfaces whose values are determined based on mean values of variables. 27,28 Table 2 shows ω and found that f (0.98) is very close to f (2.9rms) . Table 2 EL .…”
Section: Irrotational Straining Motion Rigid-body Rotation and Sheamentioning
confidence: 79%
“…6,7,25,26 Other previous studies visualize isosurfaces whose values are determined based on mean values of variables. 27,28 Table 2 shows ω and found that f (0.98) is very close to f (2.9rms) . Table 2 EL .…”
Section: Irrotational Straining Motion Rigid-body Rotation and Sheamentioning
confidence: 79%
“…It has been shown in several previous studies that A 2 exhibits a heavy-tailed pdf, characteristic of intermittency [32,33]. It has further been shown that in the conventionally used decomposition, enstrophy exhibits a pdf with a wider tail and is more intermittent than dissipation [2,3]. The pdfs of VG magnitude and its triple decomposition constituents are plotted in Fig.…”
Section: A Composition Of Vg Magnitudementioning
confidence: 88%
“…This decomposition has led to important insight into small-scale intermittency [1][2][3], intense structures in turbulence [4][5][6][7] and local streamline geometry [8][9][10]. However, recent studies [11][12][13] have shown that strain-rate and vorticity do not clearly identify the presence of normal-straining and rigid-body-rotation of the fluid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We emphasise that the small-scale fluid-velocity fluctuations in turbulence are universal [63] but not Gaussian, contrary to the statistics assumed in the statistical model. The non-Gaussian character increases as the Reynolds number increases [64]. Nevertheless, earlier comparisons between results from the statistical model and DNS often show a qualitative or even quantitative agreement [10,48,53,[65][66][67].…”
Section: Statistical Modelmentioning
confidence: 95%